To dictate or collaborate? A phenomenological exploration of physiotherapists' leadership styles. Issue 3 (13th October 2021) - Smith, Victoria; Maxwell, Claire; Robinson, Lisa
Abstract : Objectives: Selection of effective leadership styles within healthcare is linked to high quality, safe care for patients. Within the literature attention has been given to medical and nursing professions, failing to acknowledge the contribution made by physiotherapy leaders. This study aims to consider the leadership styles used by physiotherapists in a designated leadership role, specifically exploring the barriers they face and the strategies employed to overcome current leadership dilemmas. Design: A qualitative, phenomenological design was used. Consent was obtained from each participant for one semistructured interview which was audio recorded and transcribed verbatim. Framework analysis was used to analyse the data. Setting: A large National Health Service Foundation Trust within the North East of England. Participants: A purposive sample of ten physiotherapy team leaders. Results: The theoretical leadership framework that emerged demonstrated the daily tensions experienced by physiotherapy team leaders in regard to being a transactional or transformational leader. Within this, three superordinate themes exist: the individual, the team and the organisation and beyond. Each theme contained barriers and enablers which related to transactional and transformational leadership styles, respectively. Conclusions: The framework identified gives insight into a group of clinical leaders not yet explored and provides a foundation for the development of leadership behaviours throughout physiotherapy. These clinicians should be supported by senior leaders to develop more transformational styles which have the potential to impact on staff well-being and patient care. Future research should compare these findings with studies involving larger sample sizes that span the health and social care system.